Sadie and the big mountain - Korngold, Jamie S. (Kar-Ben Pub., 2012)
When her synagogue's nursery school plans a hike to celebrate Shavuot, the holiday commemorating the day the Jewish people received the Ten Commandments, Sadie is not sure she will be able to climb a huge mountain. Includes facts about the holiday and a recipe for blintzes.